Karakteristik Kesalahan Pelayanan dengan Kebijakan Keselamatan Pasien di Rumah Sakit Gigi dan Mulut Universitas Muhammadiyah Semarang - Kusniati, Retno; Kartika, Rika Widya; Sumarwanto, Edi; Arti, Dwi Windu Kinanti (LPPM Hang Tuah Pekanbaru, 2024)
Background: The field of dentistry prioritises and pays attention to patient safety because unsafe health services in the dental field result in an increase in the potential for morbidity and mortality as well as a financial burden on the health service system. In connection with health services in hospitals, errors have occurred due to the characteristics of service errors in dental and oral hospitals. Hospital staff themselves often need to correct things, including mistakes in discipline, communication, and technical errors. Patient safety is the concept of patients who are in health services so that they can achieve the expected impact. Objective: To measure the characteristics of service errors with patient safety policies at the Dental and Oral Hospital of Muhammadiyah University Semarang. Methods: This research is a quantitative descriptive study with a cross-sectional research design. A total of 68 samples were taken from dentists, young dentists and staff. Univariate analysis was assessed based on frequency distribution. Results: The highest positive response results were in the dimensions of the assessment of patient safety policies and services 95.59% were included in the very good/strong category, which means that the level of patient safety policies and benefits at RSGM Unimus was already supportive and in the assessment of internal cooperation (in units) had the lowest positive response, namely 71.64%, can be categorized as moderate so that it still needs to be improved in internal collaboration at RSGM Unimus. Conclusion: Overall, the characteristics of service errors and patient safety policies at the Muhammadiyah University Semarang Dental and Oral Hospital are good, especially in the assessment dimension of patient and service safety policies.